Giant Cell Arteritis Presenting With Multiple Cranial Neuropathies – Case Report. (April 2023) - Ye, Jessica J.; Bouffard, Marc A.; Brooks, Earllondra; Hung, Yin P.; Kimchi, Eyal Y.
Background: Vision loss accounts for most ophthalmic presentations of giant cell arteritis (GCA), but an important minority of patients present with diplopia and other cranial neuropathies. Case study: Here we present the case of an 84-year-old woman with a prior history of multiple cancers who was admitted to our hospital after developing double vision. She was found to have mydriasis, ptosis, and ophthalmoplegia in the right eye (OD) consistent with a combined R CNIII/CNVI neuropathy, as well as highly elevated inflammatory markers. Given her cancer history, the patient was initially worked up for various neoplastic, paraneoplastic, inflammatory, and infectious causes of multiple cranial neuropathies; however, as these results were negative, GCA became a more likely contender as a possible rare cause of multiple cranial neuropathies. The patient underwent temporal artery biopsy which showed pathology consistent with giant cell arteritis, and she was treated with steroids with eventual improvement in ophthalmoplegia and ptosis. Conclusions: This case illustrates the importance of recognizing GCA as a rare possible cause of multiple cranial neuropathies, including the indispensable role of temporal artery biopsy.